HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA- TANGAN DENGAN KETERAMPILAN BLOK BOLA VOLI ATLET JUNIOR PUTRA CLUB RAJAWALI PONTIANAK - Sari, Novi Aprilia; Supriatna, Eka; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThe purpose of this study was to prove the relationship between leg muscle explosivepower and eye-hand coordination on the volleyball block skills of the Rajawali ClubRajawali Pontianak Junior Athletes. This research is a correlational study. Thepopulation in this study was the male junior volleyball athlete of the Pontianak RajawaliClub. The sampling technique used was saturated sampling technique, the number ofsamples was 25 athletes. The results of the study (1) there is a significant positiverelationship between leg muscle explosive power and volleyball block skills, r count is0.832 r table 0.3961. The level of closeness in the high category, the relationshipcontribution is 69.2%. (2) there is a significant positive relationship between eye-handcoordination and volleyball block skills, r count is 0.533 r table is 0.3961. The levelof closeness of the relationship is in the medium category, the relationship contributionis 28.4%. (3) there is a significant positive relationship simultaneously (simultaneously)leg muscle explosive power and eye-hand coordination with volleyball block ability, rcount is 0.542 r table 0.3961. The level of closeness of the relationship category ismoderate, the relationship contribution is 29.3%.Keywords: Explosive power, Eye-hand coordination, Block Skill